Human body's channel modeling and low power, high data rate transceiver design for wireless capsule endoscopy - Md. Rubel Basar (School of Computer and Communication Engineering, 2013)
The main purpose of this thesis is addressing the solution of the major limitations of the present WCE system those deter the wider application of WCE in clinic.